Prodromal symptoms in hidradenitis suppurativa. (1st April 2017) - Ring, H. C.; Theut Riis, P.; Zarchi, K.; Miller, I. M.; Saunte, D. M.; Jemec, G. B.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease, which presents as recurrent nodules and sinus tracts (tunnels) with subsequent scarring, predominantly involving the intertriginous regions. Although prodromal symptoms (i.e. various symptoms preceding the eruption of the HS lesions) are often mentioned, there have been no formal investigations into this aspect. Insight into prodromal symptoms may enable patients with HS or dermatologists in choosing a more targeted treatment at a much earlier stage, potentially increasing treatment efficacy and quality of life. Aim: To characterize the spectrum of prodromes in patients with HS. Methods: An extensive questionnaire that explored the frequency, type and time of occurrence of the prodromal symptom(s) and the degree of certainty of the perceived association was administered to 72 patients. Results: The majority of the 72 patients (83.3%; n = 60) confirmed that they experienced one or more symptom(s) prior to the development of inflamed nodules or abscesses. These included: fatigue (32%), malaise (defined as a fever‐like sensation) (23%), headache (11%) and nausea (2%). Localized symptoms included skin erythema (75%), paraesthesia (63%) and itching (20%). the majority of the patients stated that the prodromes usually occurred > 24 h (45%) or 12–24 h (20%) before the eruption. Conclusion: Our data suggest that the majority of patients with HS experience prodromal symptoms, heralding a flare of their HS. The findings may give rise to important new treatment approaches for the management of HS.